The Role of Job Satisfaction in Mediating Factors Affecting Employee Performance - Olivia, Lisa; Rozak, Hasan Abdul (Jurnal Ilmiah Sumber Daya Manusia, 2023)
This study will look at and write about these things: how the work environment and pay affect job satisfaction; how the work environment and pay affect employee performance; and how job satisfaction affects employee performance. People who work for the Department of Manpower and Transmigration in the province of Central Java are part of the sample in this study. In this method, descriptive analysis is used with instruments that are tested for validity, reliability, and hypotheses that are tested. There is a link between job satisfaction and the way people work. This study shows that this is true. People who get paid are happier at work. Because of the way people work, their performance can be affected by the way they work. Compensation has an effect on how well employees work. Employees who are happy at work do a better job. Satisfaction acts as a buffer between the work environment and how well employees do their jobs. Satisfaction acts as a buffer between the effects of pay and the performance of employees.